Implementasi Model Pembelajaran Flipped Classroom dalam Mata Pelajaran Sejarah untuk Meningkatkan Pemahaman Materi - Samudra Eka Cipta; Pendi Kurniawan; Sopian Sori (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to explain the effectiveness of the implementation of the flipped classroom learning model on improving students' critical thinking skills in History subjects, especially in schools. The development of the industrial revolution 4.0 seems to open up the widest possible access, especially in the application of this method. There are several uses of online media as a means of developing this method which can then be applied by teachers in the History learning process. This study uses a quasi-experimental research type with a qualitative approach. The benefits of using this model are to activate students in learning and overcoming History Studies learning problems in schools